Fluorescence properties of several chemotherapy drugs: doxorubicin, paclitaxel and bleomycin - Motlagh, Najme Sadat Hosseini (Biomed Opt Express, 2016)
Several chemo-drugs act as the biocompatible fluorophores. Here, the laser induced fluorescence (LIF) properties of doxorubicin, paclitaxel and bleomycin are investigated. The absorption lines mostly lie over UV range according to the UV-VIS spectra. Therefore, a single XeCl laser provokes the desired transitions of the chemo-drugs of interest at 308 nm. It is shown that LIF spectra are strongly dependent on the fluorophore concentration giving rise to the sensible red shift. This happens when large overlapping area appears between absorption and emission spectra accordingly. The red shift is taken into account as a characteristic parameter of a certain chemo-drug. The fluorescence extinction (α) and self-quenching (k) coefficients are determined based on the best fitting of the adopted Lambert-Beer equation over experimental data. The quantum yield of each chemo-drug is also measured using the linearity of the absorption and emission rates.